The Influence of Digital Literacy on the Management Information System of Creative Economy Business Actors - Niska Ramadani; Fitriany (Universitas Syiah Kuala, 2026)
This study aims to empirically examine the influence of digital literacy on the utilization of Management Information Systems (MIS) among creative economy business actors in Indonesia. A quantitative associative descriptive approach was employed, with data collected from 100 respondents selected through purposive sampling. Instruments were developed using a five-point Likert scale and tested for validity and reliability prior to use. Data analysis encompassed classical assumption tests including normality, linearity, and heteroscedasticity followed by simple linear regression analysis processed through SPSS version 25. The findings confirm that digital literacy exerts a positive and significant effect on MIS utilization, yielding a regression coefficient of 0.638, a t-count of 8.986 (p = 0.000), and a determination coefficient of 45.2%. These results indicate that enhanced digital competency among business actors directly corresponds to more optimal and strategic MIS adoption in their business operations. The study underscores the urgent need for structured, contextually relevant digital literacy programs that integrate applied MIS training, targeting creative economy practitioners, industry associations, and policymakers as primary stakeholders. This research addresses a documented gap in the literature by providing the first hypothesis-driven empirical evidence of the digital literacy–MIS relationship specifically within Indonesia's creative economy sector, a population previously underrepresented in information systems and management research. The cross-sectional design and purposive sample constrain generalizability; future research should employ longitudinal approaches and broader sampling across diverse regions and creative economy sub-sectors.